Implementation of Total Quality Management in Improving the Quality of Education at State 2nd High School Tebo, Jambi Province - Ahdiyenti, Ahdiyenti; Umar, Hasbi; Anwar Us, Kasful (LPPPIPublishing, 2025)
The educational practices organized by this madrasah still have difficulty in obtaining adequate resources. The implementation process of quality management has not begun with an analysis of the identified problems. Even still felt lack of training and guidance on quality. Based on that, this study aims to analyze the implementation of total quality management (TQM) in improving the quality of education at Madrasah Aliyah Negeri 2 Tebo. This qualitative research uses a qualitative case approach. The subjects of this study were the principal of Madrasah Aliyah Negeri 2 Tebo, deputy principal, committee, administrative staff, teachers and students. Data collection with observation, interview and documentation techniques. Data analysis using the Miles and Huberman model consists of data reduction, data display and data conclusion. The results of the study indicate that the implementation of Total Quality Management (TQM) in improving the quality of education at MAN 2 Tebo is not optimal because it has not met the standards evenly in each quality component. In terms of planning, the implementation of TQM aims to create quality and superior human resources (HR) through programmed plans involving all elements of the school, including students and parents. In the implementation, the education process has been running well, although there are still obstacles in collecting data related to the effectiveness of the program and more structured communication. In terms of output and outcome, this madrasah has succeeded in implementing the superior class program, which strengthens public trust in the quality of education provided. Continuous improvement in the implementation of TQM is carried out constantly, with a focus on finding ways to improve every educational process at MAN 2 Tebo. The commitment of the head of the madrasah in implementing TQM focuses on fulfilling customer satisfaction, both from students and parents, to achieve better educational outcomes.